KEMISKINAN PERKOTAAN DAN PERDESAAN BERDASARKAN DIMENSI KESEMPATAN BERUSAHA DI KABUPATEN ROKAN HULU - Regita Nabila Aziz Putri; Dahlan Tampubolon; Taryono Taryono (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This study aims to see how the Dimensions of Business Opportunity in urban poor households and rural poor households will then be compared between differences in urban poverty, namely in Ujung Batu Village and rural poverty in Ujung Batu Timur Village in Rokan Hulu Regency through the 12 types of sub-variables used namely income, household members who work free in the field, household members who have skills outside the agricultural sector, ease of capital from banks or financial institutions, business training by the government, financial support by the government, business training by the private sector, financial support by the private sector, convenience access to business information by the government, ease of transportation facilities and infrastructure, ease of access to information through print media and the internet, as well as the majority of the age group. This study uses primary data with non-probability sampling techniques with accidental sampling with a sample size of 100 respondents in urban poverty and 50 respondents in rural poverty using a questionnaire. Using descriptive statistical methods to describe the criteria for respondents and using the cross tabulation method to describe respondents through the subvariables used. Differences in urban and rural poverty were compared through the Mann Whitney test which found that the income sub-variables, household members free field workers, ease of loan capital, financial support and business training from both the government and the private sector, as well as access to information from internet media were not significantly different. Whereas in the sub-variables of household members who have knowledge outside of agriculture, access to business information from the government, transportation infrastructure and age there are significant differences between Ujung Batu Village and Ujung Batu Timur Village.